Teaching in a third space during national COVID-19 lockdowns: in loco magister?. Issue 2 (3rd April 2021) - Johnston, David H.; Foy, Katrina; Mulligan, Aloyise; Shanks, Rachel
Abstract : The COVID-19 pandemic brought about rapid change in the way education was delivered in terms of online teaching and how this was managed by families in their homes. This study looks at the relationship between home (first space) and school (second space) and uses the concept of the 'third space' (Bhabha, H. [1994]. The Location of Culture, London: Routledge) to explore home-school links. Nine participants working in six local authorities in Scotland were questioned during the first lockdown in 2020 and then interviewed during the second national lockdown in 2021. Their responses were analysed in terms of the awareness they had of home funds of knowledge and the influence this had on their pedagogy online. The researchers investigated whether a third space had emerged and, if so, what the features of this hybrid space were. A key finding relates to the role of parents in the third space, in loco magister. In the first lockdown, glimpses of third space learning were visible in children's achievements online. In the second lockdown, however, parental concerns to preserve some semblance of orderly family life led to the colonisation of the spatio-temporal dimensions of online teaching, seeing the return to more transmissive teacher approaches and missed opportunities for children's learning.